Corporate governance and financial performance for engaging socially and environmentally responsible practices. Issue 2 (4th December 2018) - Fiandrino, Simona; Devalle, Alain; Cantino, Valter
Abstract : Purpose: This paper aims to reconcile the conflicting understanding on the nexus between corporate governance (CG), corporate financial performance (CFP) and corporate social responsibility (CSR) by investigating how companies engage with CSR practices. Design/methodology/approach: The study carries out a multivariate linear regression analysis on a sample of 361 listed companies from five countries in Europe: France, Germany, Italy, Spain and the UK. Findings: CG mechanisms and CFP have an impact on CSR because they affect social and environmental practices strongly and significantly. Furthermore, the findings describe the capacity of CSR to influence both the CG structure and the CFP. Research limitations/implications: The present research limits the analysis on the social and environmental performance of companies that communicate their commitment to stakeholders without distinguishing between "greenwashing" companies that implement CSR to improve corporate reputation and those companies that pursue effective societal benefits, taking care of stakeholder relationships. Practical implications: The CSR approach can drive the CG structure and improve CFP if managers perceive the implementation of sustainable practices as an integrated process rather than a mere outcome. Originality/value: This paper seeks to disentangle the nexus between CG, CFP and CSR, not yet precisely defined by scholars in the context of five countries in Europe.